Rachunek kosztów działań w polskich bankach spółdzielczych - Bojnowska, Agnieszka (Cost Accounting in Polish Co-Operative Banks, 2005)
Because of changes in economic conditions, in the structure of market and in carrying out an economic activity, a new method of cost allocation was needed. Activity-Based Costing is an answer - an alternative approach to estimating costs of a product/service proposed by two American professors in 80' of the last century. The paper shows the results of the research knowing and using the new method in Polish co-operative banks. As a consequence of the research, the idea of the new method, its assumptions, its advantages and disadvantages, stages of implementation and software assistance are discussed. This method is considered as the one well suited to calculate a precise cost of financial services. Using it might be a chance of achieving competitive advantage by Polish co-operative banks functioning in the open European market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 13-22